Transjugular Approach in Catheter Ablation of Ventricular Ectopy Originating from the Superior Tricuspid Annulus: An Effective Alternative to the Unsuccessful Transfemoral Approach - Cardoso, Acácio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2023)
Ventricular premature complexes originating from the tricuspid valve can be a major challenge for the electrophysiologist. Anatomical features of the tricuspid valve impose limitations for mapping and catheter ablation through the femoral vein (inferior approach). In this case, we report the elimination of a ventricular ectopy by radiofrequency catheter ablation through the transjugular approach after three unsuccessful attempts through the inferior approach.